Honey roasted - Coyle, Cleo (Coyle, Cleo. Coffeehouse mystery ;, 2023)
"Clare Cosi is busy as a bee planning her honeymoon when murder buzzes into the Village Blend in this all-new mystery in the beloved New York Times bestselling Coffeehouse Mysteries by Cleo Coyle. While struggling to find a romantic (and affordable) destination for her upcoming honeymoon, coffeehouse manager Clare Cosi whips up a honey of a drink made from honey-processed coffee. Clare plans to serve her outstanding new Honey-Cinnamon Latte at her spring wedding to her longtime honey, NYPD detective Mike Quinn. The culinary world is also abuzz about the amazing honey that Clare was lucky enough to source for her shop's new latte. Produced by Madame's old friend "Queen" Bea Hastings, the rare, prize-winning nectar from Bea's rooftop hives commands a premium price, and top chefs compete for a chance to use it in their signature seasonal dishes. One night, a swarm of escaped bees blanket the Village Blend's chimney, and Clare discovers Bea's unconscious body after she seemingly fell from her elaborate high-rise rooftop greenhouse. The police want to rule it as a tragic accident or possible attempted suicide, but Clare does not believe either theory. Like Madame, she knows this Queen would never abandon her hive. To sort out this mystery, Clare investigates a world of cutthroat chefs, culinary start-ups, and competitive urban beekeepers. But can she uncover the truth without getting stung? Includes recipes fit for a queen bee!"--